2016
DOI: 10.1371/journal.pone.0151465
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Primitive Neuroectodermal Tumors of the Central Nervous System Differentially Express Granzyme Inhibitors

Abstract: BackgroundCentral nervous system (CNS) primitive neuroectodermal tumors (PNETs) are malignant primary brain tumors that occur in young infants. Using current standard therapy, up to 80% of the children still dies from recurrent disease. Cellular immunotherapy might be key to improve overall survival. To achieve efficient killing of tumor cells, however, immunotherapy has to overcome cancer-associated strategies to evade the cytotoxic immune response. Whether CNS-PNETs can evade the immune response remains unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…We found that six out of 26 tumors acquired expression of SerpinB1 (23%) and 13 out of 26 tumors SerpinB4 (50%). In contrast to CNS-PNETs, 17 we did not find expression of SerpinB9 in pediatric medulloblastoma ( Fig. 2B ).…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…We found that six out of 26 tumors acquired expression of SerpinB1 (23%) and 13 out of 26 tumors SerpinB4 (50%). In contrast to CNS-PNETs, 17 we did not find expression of SerpinB9 in pediatric medulloblastoma ( Fig. 2B ).…”
Section: Resultscontrasting
confidence: 64%
“…Immunohistochemistry was carried out on 4 μm thick formalin fixed paraffin embedded consecutive sections as described before by Vermeulen et al. 17 Immunohistochemistry for PD-1 (Abcam clone NAT105, ab52587) 1:50 and PD-L1 (Abcam clone 28-8, ab205921) 1:50 was performed using an automated immunostainer (Benchmark Ultra, Ventana, Roche). Immunohistochemistry for myeloperoxidase (MPO) (Leica Biosystems Novocastra clone 59A5) was performed manually.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also expressed in accessory immune cells, such as dendritic cells, where it plays a role in presenting antigens 67 . SERPINB9 could contribute to immune evasion in leukemia cells 68 and to overcoming intracellular cytotoxicity in neuroectodermal tumors 69 . It has also been involved in autoimmune diseases 70 , such as celiac disease 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mTOR potently induced IDO1 expression and activity, corroborating its ability to recruit Treg cells in the tumor microenvironment, which is the mechanism by which mTOR-targeted therapy fails. More recently, one report showed that central nervous system primitive neuroectodermal tumors are capable of evading immune recognition by downregulating the expression of their cell surface MHC-I and CD1d, and by overexpressing granzyme inhibitors SERPINB9, SERPINB1, and SERPINB4 [85]. Another study found that genetically downregulating Treg TGF-β signaling nearly abolished Treg cells and inhibited medulloblastoma progression via CD8 + cytotoxic T-lymphocyte attack [86].…”
Section: Immune Evasionmentioning
confidence: 99%